Proposed transit park at Jalan Hang Kasturi, Kuala Lumpur - Said, Ismail (2007)
This development proposal is to design and plan an urban transit park located at Jalan Hang Kasturi in Kuala Lumpur. This area comprised of two major centers: the Central Market which is a Malaysia center of cultural, art and heritage, and the Central Market Putra LRT Station. Its strategic location acts as a collection and dispersion point of people to come from or to go to other nodes, for example, Puduraya bus station. The overall development concept is The Magnets which attract and encourage people to gather or disperse. This proposal intends to solve two issues; firstly, traffic congestion that causes air pollution to the city, and secondly, lack of a proper waiting area including facilities and amenities for people to feel safe, secure and comfort. The proposal divides the site into three major zones, active, semi-active and passive, based on people activities. The active zone is a cultural place for people located at the main entrance of the Central Market. It comprise of pedestrian mall, mini amphitheatre, outdoor eating area and a multi-functional open space. The semi-active zone offers the people for outdoor performances such as traditional dance and aerobic dance as well as children play area. Finally, the passive zone is located at the south-end of the site which composes of a promenade for relaxation and rest, and greenery made up of undulating lawn and kiosks. This proposal creates a continuity of pedestrian movement linking the Central Market to the surrounding areas allowing the site to become more vibrant with people’s activities. The hard landscape elements apply the concept of the public art and verticality of wall and fence to attract the intention of people. Likewise, the soft landscape elements apply the approach of dense and formality planting to provide shade and identity to the site.